Cross-sections for photonuclear reactions ⁹³Nb(γ,n)⁹²ᵐNb and ⁹³Nb(γ,n)⁹²ᵗNb in the end-point bremsstrahlung energies 36…91 MeV - Vodin, A.N.; Deiev, O.S.; Timchenko, I.S.; Olejnik, S.N.; Kachan, A.S.; Korda, L.P.; Kuplennikov, E.L.; Kushnir, V.A.; Mytrochenko, V.V.; Perezhogin, S.A.; Pilipenko, N.N.; Trubnikov, V.S. (Вопросы атомной науки и техники, 2020)
The flux-weighted averaged over the energy range of bremsstrahlung spectrum from reaction threshold up to the maximum energy of γ-ray cross-sections <σ (E)> of the ⁹³Nb(γ,n)⁹²ᵐNb and ⁹³Nb(γ,n)⁹²ᵗNb photonuclear reactions were determined by the gamma-activation method within the end-point bremsstrahlung energies Еγmax = 36…91 MeV. Activation of ⁹³Nb targets has been done by a bremsstrahlung flux using an electron beam at the linear accelerator LUE-40 at RDC “Accelerator” NSC KIPT. The γ-ray spectra of irradiated targets were registered using the HPGe detector with an energy resolution of 1.8 keV for the 1332 keV line ⁶⁰Co. To control the bremsstrahlung flux we used ⁿᵃᵗMo witness-targets and a reaction cross-section of ¹⁰⁰ Mo(γ,n)⁹⁹Mo. Obtained experimental cross-sections <σ(E)> of the studied reactions are in good agreement with the theoretical values calculated within TALYS 1.9 code and the results of other authors. The averaged cross-sections <σ(E)> of the ⁹³Nb(γ,n)⁹²ᵐNb and ⁹³Nb(γ,n)⁹²ᵗNb reactions in the energy range 35…45 MeV and > 70 MeV were obtained for the first time. Виміряні усереднені за гальмівним спектром перерізи <σ (E)> фотоядерних реакцій ⁹³Nb(γ,n)⁹²ᵐNb і ⁹³Nb(γ,n)⁹²ᵗNb в енергетичному інтервалі від порога реакції до граничних енергій Еγmax = 36…91 MeV. Дослідження проведені на пучку лінійного прискорювача електронів ЛУЕ-40 НІК «Прискорювач» ННЦ ХФТІ з використанням мішеней ⁹³Nb та за допомогою гамма-активаційного методу. Спектри γ-випромінювання активованих зразків реєструвалися HPGe-детектором з енергетичним розрізненням 1,8 кеВ по лінії 1332 кеВ ⁶⁰Co. Для контролю потоку гальмівних γ-квантів використовувалися мішені-свідки з натурального молібдену і переріз реакції ¹⁰⁰Mo(γ,n)⁹⁹Mo. Експериментальні перерізи <σ (E)> досліджуваних реакцій знаходяться в задовільному узгодженні з теоретичними значеннями, отриманими за допомогою програмного коду TALYS 1.9 з параметрами за замовчуванням. Перерізи <σ (E)> реакцій ⁹³Nb(γ,n)⁹²ᵐNb і ⁹³Nb(γ,n)⁹²ᵗNb у діапазоні 35… 45 MэВ и >70 MэВ виміряні вперше. Измерены усредненные по тормозному γ-спектру сечения <σ (E)> фотоядерных реакций ⁹³Nb(γ,n)⁹²ᵐNb и ⁹³Nb(γ,n)⁹²ᵗNb в энергетическом интервале от порога реакции до граничных энергий Еγmax = 36…91 MeV. Исследования проведены на пучке линейного ускорителя электронов ЛУЭ-40 НИК «Ускоритель» ННЦ ХФТИ с использованием мишеней ⁹³Nb и с применением гамма-активационного метода. Спектры γ-излучения облученных образцов регистрировались HPGe-детектором с энергетическим разрешением 1,8 кэВ по γ-линии 1332 кэВ ⁶⁰Co. Для контроля потока тормозных γ-квантов использованы мишени-свидетели из натурального молибдена и сечение реакции ¹⁰⁰Mo(γ,n)⁹⁹Mo. Экспериментальные сечения <σ (E)> исследуемых реакций находятся в удовлетворительном согласии с теоретическими значениями, полученными при использовании программного кода TALYS 1.9 с параметрами по умолчанию. Сечения <σ (E)> для реакций ⁹³Nb(γ,n)⁹²ᵐNb и ⁹³Nb(γ,n)⁹²ᵗNb в области 35…45 MэВ и > 70 MэВ измерены впервые.